(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Yoga breathing which is known as pranayama yoga is the first step toward re-orienting and improving the functioning of your mind and body by learning to optimize the breathing process. The Yogis were the first to discover the importance of oxygen and breathe control and devised an exact science of breathing. They called it PRANA-YAMA, from the Sanskrit word prana meaning breath, and Yama, its control or cessation. Pranayama includes following correct breathing technique and breath control.